KELAYAKAN POP UP BOOKMATERI KEANEKARAGAMAN HAYATI DARI BUAH RANDUM, SALAK HUTAN DAN AROKPUTIH - Roviah, Roviah; Daningsih, Entin; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the feasibility of pop up book media on biodiversity material of high school in class X students from the morphology and nutrient content as well as fruit fiber ofÂ randum (Ceiba pentandra Gaertn), salak hutan (Salacca affinis), and arok putih (Ficus schwarzii Koord), found in Sibohe Pajintan Singkawang forest, Singkawang City, West Kalimantan. The research was descriptive by using purposive sampling technique with two stages, namely instrument validation and media validation. Pop up book Media was validated by five validators with 12 criteria and calculated using CVR and CVI Lawshe analysis methods. The validators were two biology education lecturers, while the other three validators were high school biology teachers the 2013 curriculum. UsingÂ questionnaires containing six aspects and 12 criteria were used as instrument. The results of instrument validation showed that the questionnaire could be used and corrected while the results of the validation of the pop up book media obtained CVR and CVI value of 0.99 which corresponded to the minimum CVR value of Lawshe for five validators, so the pop up book media was categorized valid and feasible as a learning media for biodiversity material in class X high school.Keywords:Biodiversity, Pop up book, Randum, Salak Hutan, dan Arok Putih